2007
DOI: 10.1111/j.1440-1746.2006.04698.x
|View full text |Cite
|
Sign up to set email alerts
|

Significant correlations between severe fatty liver and risk factors for metabolic syndrome

Abstract: Background and Aim: It is known that ultrasonography (US) cannot differentiate between non-alcoholic fatty liver disease (NAFLD) and steatohepatitis. However, US can accurately estimate the severity of the steatosis. The clinical significance of severe hepatic fatty change by US has not been explored. The aim of this study was to investigate the relationship between the severity of the fatty liver, classified by US, and the degree of metabolic disorders with insulin resistance. Methods: In 16 486 Taiwanese pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
75
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(90 citation statements)
references
References 48 publications
11
75
0
3
Order By: Relevance
“…In the present study, the presence of LS on abdominal ultrasound was associated with fasting insulin and total cholesterol, similar to fi ndings previously reported by other authors in non-HBV patients 25,[27][28][29] , indicating that LS is related to disordered metabolism of blood glucose and lipids. Although BMI data were available only in a small subset of patients (n = 19), these data revealed a signifi cant difference between the two study groups.…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, the presence of LS on abdominal ultrasound was associated with fasting insulin and total cholesterol, similar to fi ndings previously reported by other authors in non-HBV patients 25,[27][28][29] , indicating that LS is related to disordered metabolism of blood glucose and lipids. Although BMI data were available only in a small subset of patients (n = 19), these data revealed a signifi cant difference between the two study groups.…”
Section: Discussionsupporting
confidence: 80%
“…This finding indicates that not only was basal gluconeogenesis reduced in the HFD-fed siTORC2 mice, but hepatic insulin sensitivity was also improved in these mice. Hepatic steatosis is a characteristic feature of HFD-fed mice and other insulin-resistant/diabetic states (13,24,25), and, this abnormality was prevented in HFD-fed siTORC2 mice (Fig. 4E).…”
Section: Glucose Homeostasis and Insulin Sensitivity In Torc2 Sirna-tmentioning
confidence: 97%
“…26,27 Hepatic steatosis, even nonalcoholic steatohepatitis (NASH), is a liver disease that occurs in the absence of alcohol abuse and is frequently related to MS and type 2 diabetes. 12 We have previously reported that the severity of hepatic steatosis as assessed by ultrasound (B-mode, 3.5 MHz convex transducer) is significantly correlated with the results of hepatic enzyme tests such as AST, ALT and GGT (Po0.001); 15 however, whether hepatic steatosis can lead to abnormal hepatic enzyme test results remains controversial. [27][28][29] Regarding the relationship between MS and abnormal liver function, Miyatake et al…”
Section: Discussionmentioning
confidence: 99%